Product Upgrading Analysis of Instant Coffee Industry: A Case Study of Kapal Api Group - Asmia Inayah; Filasafia Marsya Ma’rifat; Maula Hudaya; Rizky Anggia Putri (Journal of World Trade Studies, 2021)
Kapal Api Group as the lead firm of the coffee industry in Indonesia has become one of the main players in the global value chain. This achievement cannot be separated from the upgrading strategy implemented by Kapal Api from upstream to downstream. This research examines the global value chain of PT Kapal Api Global by analyzing the upgrading strategy that focuses on functional upgrading and intersectoral upgrading. Besides that, this research also further reviews how the company synergizes with government and non-governmental actors, as well as explores the implementation of domestic and international norms at PT Kapal Api Global. Through all the information and data obtained, the authors also provide four upgrading solutions or recommendations that can be implemented by PT Kapal Api Global in the future, such as product innovation and expansion, involvement of cultural elements, marketing strategies abroad, and cooperation with non-governmental organizations.